Strategi Hukum Tata Negara Progresif Mencegah Politik Uang Pemilu Serentak - Riewanto, Agus (Integritas : Jurnal Antikorupsi, 2019)
This article examines the strategy of constitutional law from a progressive perspective in preventing money politics in simultaneous elections. The practice of money politics in every election always occurs in Indonesia, but all conventional constitutional law efforts have not been able to nullify it. So a progressive constitutional governance strategy is needed, which is to find new ways (role breaking) and innovative breakthroughs if the normative and normative legal methods are not able to immediately realize the goal of elections with integrity. This progressive prevention is carried out from upstream to downstream. A number of progressive strategic ideas from constitutional law aspects that can be done to prevent money politics include: First, the progressive arrangement changes the model of the electoral system from liberal to competitive; Secondly, progressive regulation of restrictions on candidate campaign resources and political parties; Third, the progressive arrangement of campaign money electronic transactions; Fourth, the progressive regulation on the prohibition of corruptor candidates; Fifth, the progressive arrangement of political parties' coalitions and the selection of democratic candidates; Sixth, the progressive arrangement for the cancellation of election-winning political parties that conduct money politics by the Constitutional Court; Seventh, the progressive regulation of the obligations of political parties to educate anti-money politic to their constituents; Eighth, progressive regulation of election organizers with integrity. Keywords: Progressive of Contitutional Law, Strategy Preventing and Money Politic